Elliptic tales: curves, counting, and number theory - Ash, Avner; Gross, Robert (Princeton University Press, 2012)
Elliptic Tales describes the latest developments in number theory by looking at one of the most exciting unsolved problems in contemporary mathematics--the Birch and Swinnerton-Dyer Conjecture. The Clay Mathematics Institute is offering a prize of